A review of the conundrum of mild hypoxic-ischemic encephalopathy: Current challenges and moving forward. (May 2018) - Chalak, Lina; Latremouille, Samantha; Mir, Imran; Sánchez, Pablo J.; Sant'Anna, Guilherme
Abstract: A review of the conundrum called mild hypoxic-ischemic encephalopathy (HIE) is provided. During the past decades, the definition of HIE has evolved to accommodate the short window of time required for the initiation of therapeutic hypothermia. Also, neurological evaluations have changed with the use of simpler staging systems that can be applied within the first 6 h of life. In this review, we discuss the challenges in the identification of newborns with "mild HIE" within 6 h after birth, the limitations in the existing early biomarkers of brain injury, and the current knowledge gaps in the long term neurodevelopmental outcomes of infants diagnosed with mild HIE. Progress in the understanding of mild HIE and its sequelae continues to be hindered by the lack of a standardized definition for mild HIE that will reliably identify at-risk infants who may benefit from neuroprotective strategies.